Electron interactions with the heteronuclear carbonyl precursor H2FeRu3(CO)13 and comparison with HFeCo3(CO)12: from fundamental gas phase and surface science studies to focused electron beam induced deposition - P, Ragesh Kumar T; Weirich, Paul; Hrachowina, Lukas; Hanefeld, Marc; Bjornsson, Ragnar; Hrodmarsson, Helgi Rafn; Barth, Sven; Fairbrother, D. Howard; Huth, Michael; Ingólfsson, Oddur (Beilstein Journal of Nanotechnology, 2018)
In the current contribution we present a comprehensive study on the heteronuclear carbonyl complex H2FeRu3(CO)13 covering its low energy electron induced fragmentation in the gas phase through dissociative electron attachment (DEA) and dissociative ionization (DI), its decomposition when adsorbed on a surface under controlled ultrahigh vacuum (UHV) conditions and exposed to irradiation with 500 eV electrons, and its performance in focused electron beam induced deposition (FEBID) at room temperature under HV conditions. The performance of this precursor in FEBID is poor, resulting in maximum metal content of 26 atom % under optimized conditions. Furthermore, the Ru/Fe ratio in the FEBID deposit (≈3.5) is higher than the 3:1 ratio predicted. This is somewhat surprising as in recent FEBID studies on a structurally similar bimetallic precursor, HFeCo3(CO)12, metal contents of about 80 atom % is achievable on a routine basis and the deposits are found to maintain the initial Co/Fe ratio. Low temperature (≈213 K) surface science studies on thin films of H2FeRu3(CO)13 demonstrate that electron stimulated decomposition leads to significant CO desorption (average of 8–9 CO groups per molecule) to form partially decarbonylated intermediates. However, once formed these intermediates are largely unaffected by either further electron irradiation or annealing to room temperature, with a predicted metal content similar to what is observed in FEBID. Furthermore, gas phase experiments indicate formation of Fe(CO)4 from H2FeRu3(CO)13 upon low energy electron interaction. This fragment could desorb at room temperature under high vacuum conditions, which may explain the slight increase in the Ru/Fe ratio of deposits in FEBID. With the combination of gas phase experiments, surface science studies and actual FEBID experiments, we can offer new insights into the low energy electron induced decomposition of this precursor and how this is reflected in the relatively poor performance of H2FeRu3(CO)13 as compared to the structurally similar HFeCo3(CO)12.
Keywords: dissociative electron attachment; dissociative ionization; electron induced deposition; electron molecule interaction; focused electron beam induced deposition; heteronuclear FEBID precursors; surface science

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Bret, T.; Utke, I.; Hoffmann, P. (Microelectron. Eng., 2005)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stöger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Microelectron. Eng., 2015)

(untitled) - Winkler, R.; Schmidt, F.-P.; Haselmann, U.; Fowlkes, J. D.; Lewis, B. B.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Sachser, R.; Reith, H.; Huzel, D.; Winhold, M.; Huth, M. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2013)

(untitled) - Plank, H.; Noh, J. H.; Fowlkes, J. D.; Lester, K.; Lewis, B. B.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Lewis, B. B.; Stanford, M. G.; Fowlkes, J. D.; Lester, K.; Plank, H.; Rack, P. D. (Beilstein J. Nanotechnol., 2015)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Puydinger dos Santos, M. V.; Velo, M. F.; Domingos, R. D.; Zhang, Y.; Maeder, X.; Guerra-Nuñez, C.; Best, J. P.; Béron, F.; Pirota, K. R.; Moshkalev, S.; Diniz, J. A.; Utke, I. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Begun, E.; Dobrovolskiy, O. V.; Kompaniiets, M.; Sachser, R.; Gspan, C.; Plank, H.; Huth, M. (Nanotechnology, 2015)

(untitled) - Dobrovolskiy, O. V.; Kompaniiets, M.; Sachser, R.; Porrati, F.; Gspan, C.; Plank, H.; Huth, M. (Beilstein J. Nanotechnol., 2015)

(untitled) - Silvis-Cividjian, N.; Hagen, C. W.; Leunissen, L. H. A.; Kruit, P. (Microelectron. Eng., 2002)

(untitled) - Botman, A.; De Winter, D. A. M.; Mulders, J. J. L. (J. Vac. Sci. Technol., B, 2008)

(untitled) - Schaefer, J.; Hoelzl, J. (Thin Solid Films, 1972)

(untitled) - Ohya, K.; Harada, A.; Kawata, J.; Nishimura, K. (Jpn. J. Appl. Phys., Part 1, 1996)

(untitled) - Schou, J. (Phys. Rev. B, 1980)

(untitled) - Thorman, R. M.; T. P., R. K.; Fairbrother, D. H.; Ingólfsson, O. (Beilstein J. Nanotechnol., 2015)

(untitled) - Ingólfsson, O.; Weik, F.; Illenberger, E. (Int. J. Mass Spectrom. Ion Processes, 1996)

(untitled) - Bald, I.; Langer, J.; Tegeder, P.; Ingólfsson, O. (Int. J. Mass Spectrom., 2008)

(untitled) - Böhler, E.; Warneke, J.; Swiderek, P. (Chem. Soc. Rev., 2013)

Electron-Molecule Interactions and their Applications - Christophoru, L. G. (Academic Press, 1984)

(untitled) - Hotop, H.; Ruf, M.-W.; Allan, M.; Fabrikant, I. I. (Adv. At., Mol., Opt. Phys., 2003)

(untitled) - Arumainayagam, C. R.; Lee, H.-L.; Nelson, R. B.; Haines, D. R.; Gunawardane, R. P. (Surf. Sci. Rep., 2010)

Advances In Atomic, Molecular, and Optical Physics - Fabrikant, I. I.; Eden, S.; Mason, N. J.; Fedor, J. (Chapter Nine - Recent Progress in Dissociative Electron Attachment: From Diatomics to Biomolecules, 2017)

(untitled) - Engmann, S.; Stano, M.; Matejčík, Š.; Ingólfsson, O. (Angew. Chem., Int. Ed., 2011)

(untitled) - Engmann, S.; Stano, M.; Papp, P.; Brunger, M. J.; Matejčík, Š.; Ingólfsson, O. (J. Chem. Phys., 2013)

(untitled) - May, O.; Kubala, D.; Allan, M. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Allan, M. (J. Chem. Phys., 2011)

(untitled) - Wnorowski, K.; Stano, M.; Matias, C.; Denifl, S.; Barszczewska, W.; Matejčík, Š. (Rapid Commun. Mass Spectrom., 2012)

(untitled) - Engmann, S.; Stano, M.; Matejčík, Š.; Ingólfsson, O. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Lacko, M.; Papp, P.; Wnorowski, K.; Matejčík, Š. (Eur. Phys. J. D, 2015)

(untitled) - Thorman, R. M.; Brannaka, J. A.; McElwee-White, L.; Ingólfsson, O. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Thorman, R. M.; Bjornsson, R.; Ingólfsson, O. (Eur. Phys. J. D, 2016)

(untitled) - T. P., R. K.; Barth, S.; Bjornsson, R.; Ingólfsson, O. (Eur. Phys. J. D, 2016)

(untitled) - Kumar T P, R.; Bjornsson, R.; Barth, S.; Ingólfsson, O. (Chem. Sci., 2017)

(untitled) - Zlatar, M.; Allan, M.; Fedor, J. (J. Phys. Chem. C, 2016)

(untitled) - Landheer, K.; Rosenberg, S. G.; Bernau, L.; Swiderek, P.; Utke, I.; Hagen, C. W.; Fairbrother, D. H. (J. Phys. Chem. C, 2011)

(untitled) - Rosenberg, S. G.; Barclay, M.; Fairbrother, D. H. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Rosenberg, S. G.; van Dorp, W. F.; Madey, T. E.; Hagen, C. W.; Fairbrother, D. H. (J. Phys. Chem. C, 2009)

(untitled) - Hedhili, M. N.; Bredehoft, J. H.; Swiderek, P. (J. Phys. Chem. C, 2009)

(untitled) - Rosenberg, S. G.; Barclay, M.; Fairbrother, D. H. (J. Phys. Chem. C, 2013)

(untitled) - Hauchard, C.; Rowntree, P. A. (Can. J. Chem., 2011)

(untitled) - Spencer, J. A.; Wu, Y.-C.; McElwee-White, L.; Fairbrother, D. H. (J. Am. Chem. Soc., 2016)

(untitled) - Spencer, J. A.; Brannaka, J. A.; Barclay, M.; McElwee-White, L.; Fairbrother, D. H. (J. Phys. Chem. C, 2015)

(untitled) - Spencer, J. A.; Rosenberg, S. G.; Barclay, M.; Wu, Y.-C.; McElwee-White, L.; Fairbrother, D. H. (Appl. Phys. A, 2014)

(untitled) - Masaki, T.; Masayuki, S.; Kazuo, F. (Nanotechnology, 2005)

(untitled) - Lukasczyk, T.; Schirmer, M.; Steinrück, H.-P.; Marbach, H. (Small, 2008)

(untitled) - Rodríguez, L. A.; Deen, L.; Córdoba, R.; Magén, C.; Snoeck, E.; Koopmans, B.; De Teresa, J. M. (Beilstein J. Nanotechnol., 2015)

(untitled) - Lavrijsen, R.; Córdoba, R.; Schoenaker, F. J.; Ellis, T. H.; Barcones, B.; Kohlhepp, J. T.; Swagten, H. J. M.; Koopmans, B.; Teresa, J. M. D.; Magén, C.; Ibarra, M. R.; Trompenaars, P.; et al. (Nanotechnology, 2011)

(untitled) - Fernández-Pacheco, A.; Teresa, J. M. D.; Córdoba, R.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Serrano-Ramón, L.; Córdoba, R.; Rodríguez, L. A.; Magén, C.; Snoeck, E.; Gatel, C.; Serrano, I.; Ibarra, M. R.; De Teresa, J. M. (ACS Nano, 2011)

(untitled) - Córdoba, R.; Sharma, N.; Kölling, S.; Koenraad, P. M.; Koopmans, B. (Nanotechnology, 2016)

(untitled) - Vollnhals, F.; Woolcot, T.; Walz, M.-M.; Seiler, S.; Steinruck, H.-P.; Thornton, G.; Marbach, H. (J. Phys. Chem. C, 2013)

(untitled) - Muthukumar, K.; Jeschke, H. O.; Valentí, R.; Begun, E.; Schwenk, J.; Porrati, F.; Huth, M. (Beilstein J. Nanotechnol., 2012)

(untitled) - Scheuer, V.; Koops, H.; Tschudi, T. (Microelectron. Eng., 1986)

(untitled) - Noh, J. H.; Stanford, M. G.; Lewis, B. B.; Fowlkes, J. D.; Plank, H.; Rack, P. D. (Appl. Phys. A, 2014)

(untitled) - Porrati, F.; Kämpken, B.; Terfort, A.; Huth, M. (J. Appl. Phys., 2013)

(untitled) - Winhold, M.; Schwalb, C. H.; Porrati, F.; Sachser, R.; Frangakis, A. S.; Kämpken, B.; Terfort, A.; Auner, N.; Huth, M. (ACS Nano, 2011)

(untitled) - Porrati, F.; Begun, E.; Winhold, M.; Schwalb, C. H.; Sachser, R.; Frangakis, A. S.; Huth, M. (Nanotechnology, 2012)

(untitled) - Porrati, F.; Sachser, R.; Gazzadi, G. C.; Frabboni, S.; Huth, M. (J. Appl. Phys., 2016)

(untitled) - Porrati, F.; Pohlit, M.; Müller, J.; Barth, S.; Biegger, F.; Gspan, C.; Plank, H.; Huth, M. (Nanotechnology, 2015)

(untitled) - Kruglyak, V. V.; Demokritov, S. O.; Grundler, D. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Joshi, V. K. (Eng., Sci. Technol., Int. J., 2016)

(untitled) - Pablo-Navarro, J.; Sanz-Hernández, D.; Magén, C.; Fernández-Pacheco, A.; de Teresa, J. M. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Pohlit, M.; Porrati, F.; Huth, M.; Ohno, Y.; Ohno, H.; Müller, J. (J. Magn. Magn. Mater., 2016)

(untitled) - Pohlit, M.; Stockem, I.; Porrati, F.; Huth, M.; Schröder, C.; Müller, J. (J. Appl. Phys., 2016)

(untitled) - Gilmore, C. J.; Woodward, P. (J. Chem. Soc. A, 1971)

(untitled) - Patiny, L.; Borel, A. (J. Chem. Inf. Model., 2013)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Adamo, C.; Barone, V. (J. Chem. Phys., 1999)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Zheng, J.; Xu, X.; Truhlar, D. G. (Theor. Chem. Acc., 2011)

(untitled) - Barber, M.; Connor, J. A.; Guest, M. F.; Hall, M. B.; Hillier, I. H.; Meredith, W. N. E. (Faraday Discuss. Chem. Soc., 1972)

(untitled) - Plummer, E. W.; Salaneck, W. R.; Miller, J. S. (Phys. Rev. B, 1978)

(untitled) - T. P., R. K.; Unlu, I.; Barth, S.; Ingólfsson, O.; Fairbrother, D. H. (J. Phys. Chem. C, 2018)

Handbook of X-ray Photoelectron Spectroscopy: A Reference Book of Standard Spectra for Identification and Interpretation of XPS Data - Moulder, J. F.; Chastain, J. (Physical Electronics, 1995)

(untitled) - Johannesson, G. H.; Wang, H.; Kvaran, A. (J. Mol. Spectrosc., 1996)

(untitled) - Li, Z.; Milosavljević, A. R.; Carmichael, I.; Ptasinska, S. (Phys. Rev. Lett., 2017)

(untitled) - Fernandez-Pacheco, A.; Streubel, R.; Fruchart, O.; Hertel, R.; Fischer, P.; Cowburn, R. P. (Nat. Commun., 2017)

(untitled) - Keller, L.; Mamoori, M. A.; Pieper, J.; Gspan, C.; Stockem, I.; Schröder, C.; Barth, S.; Winkler, R.; Plank, H.; Pohlit, M.; Muller, J.; Huth, M. (Nat. Commun., 2017)

Superconductivity in Nanowires - Fabrication and Quantum Transport - Bezryadin, A. (Wiley-VCH, 2012)

(untitled) - Sangiao, S.; Morellón, L.; Ibarra, M. R.; De Teresa, J. M. (Solid State Commun., 2011)

(untitled) - Winhold, M.; Weirich, P. M.; Schwalb, C. H.; Huth, M. (Appl. Phys. Lett., 2014)

(untitled) - Weirich, P. M.; Winhold, M.; Schwalb, C. H.; Huth, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Huth, M.; Porrati, F.; Dobrovolskiy, O. V. (Microelectron. Eng., 2018)

(untitled) - Winhold, M.; Weirich, P. M.; Schwalb, C. H.; Huth, M. (Nanofabrication, 2014)

(untitled) - Porrati, F.; Sachser, R.; Schwalb, C. H.; Frangakis, A. S.; Huth, M. (J. Appl. Phys., 2011)

(untitled) - Sachser, R.; Porrati, F.; Schwalb, C. H.; Huth, M. (Phys. Rev. Lett., 2011)

(untitled) - Chini, P.; Colli, L.; Peraldo, M. (Gazz. Chim. Ital., 1960)

(untitled) - Geoffroy, G. L.; Gladfelter, W. L. (J. Am. Chem. Soc., 1977)

Synthetic Methods of Organometallic and Inorganic Chemistry - Herrmann, W. A. (Thieme Verlag, 2014)

(untitled) - Bjarnason, E. H.; Ómarsson, B.; Engmann, S.; Ómarsson, F. H.; Ingólfsson, O. (Eur. Phys. J. D, 2014)

(untitled) - Neese, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2012)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Perdew, J. P. (Phys. Rev. B, 1986)

(untitled) - Humphrey, W.; Dalke, A.; Schulten, K. (J. Mol. Graphics, 1996)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Rosenberg, S. G.; van Dorp, W. F.; Madey, T. E.; Hagen, C. W.; Fairbrother, D. H. (J. Appl. Phys., 2010)

(untitled) - Tanuma, S.; Powell, C. J.; Penn, D. R. (Surf. Interface Anal., 1991)